(3GdefGgd GdUGajI aj TQM eYGfi GdTGajIs - (3dWa Gddg Hf eMeO GdZjGK GdXajQj, bWH GdOjf,J (B1035 (3g` s ((3Ydi Hf jMji (B()(3? s)
(3ChdgG (B:s
(3Chd GdehLhO(B: (3agh dZI gPjd hbO JcSQ GdYjf s
(3BNQgG (B:s
(3hGdMeO ddg QH GdYGdejf MeOG cKjQG, hUdi Gddg Ydi SjOfG eMeO hBdg hSde UdGI OGFeI eJUdI ef jhefG gPG Edi jhe GdOjf s
(3GdfSNI HgG MhGTs
(3GdfU TQM dcJGH GdTGajI aj GdJUQja dGHf GdMGLH (B- (3J (B646 (3g`s
(3HgG fXGe GdJYbjHIs
(3cJH GdfU GdeTQhM HGdeOGO GdCMeQ s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdUQas